Neonatal Hearing Screening Using Wideband Absorbance and Otoacoustic Emissions Measured Under Ambient and Pressurized Conditions - Carolina Verônica Lino Novelli; Milaine Dominici Sanfins; Piotr Henryk Skarżyński; Magdalena Beata Skarżyńska; Thaís Antonelli Diniz-Hein; Maria Francisca Colella-Santos (Children)
Background: The objective was to analyze wideband acoustic absorbance and transiently evoked otoacoustic emissions (TEOAEs) from newborns without risk indicators of hearing loss and test the effectiveness of measuring TEOAEs under pressurized ear canal conditions. Methods: Evaluation of 102 newborns from a maternity hospital, who stayed in the well-baby nursery and did not have risk indicators for hearing loss. The procedures involved wideband tympanometry and TEOAEs performed at ambient pressure (AP) and at a pressure corresponding to maximum compliance (PP). Newborns were then divided into three groups according to their AP and PP results: G1 (PASS/PASS), G2 (FAIL/PASS), and G3 (FAIL/FAIL). Results: Comparing the three groups, pressurization improved the pass rate for G2 only. For wideband absorbance, differences were statistically significant for frequencies of 2, 3, and 6 kHz, with lower values under the AP condition. For TEOAEs, the differences were statistically significant in all bands, with lower values under the AP condition. Conclusions: Pressurization was effective in detecting more TEOAEs in G2, thus reducing the number of failures in neonatal hearing screening and reducing the need to return for retesting.